2012
DOI: 10.4236/cm.2012.31006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activity on Xanthine Oxidase and Antioxidant Properties of <i>Teucrium polium</i>

Abstract: The antioxidative activities of subfractions; methanol (CE), chloroform (CHE) and ethyl acetate (EAE) of Teucrium polium extracts (TPE) were investigated. HPLC analysis of the plant revealed the existence of procyanidins B 1 and B 2 , gallic acid, catechin and epicatechin. All the extracts showed inhibitory properties on xanthine oxidase, with IC 50 ranging from 0.80 ± 0.07 to 11.76 ± 0.50 µM/quercetin equivalent. In the cellular system, all the extracts showed a protective effect greater than those of quercet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Thus, the degradation rate of β-carotene-linoleate depends on the antioxidant activity of the extracts. According to Boumerfeg et al [ 22 ], the test of linoleic acid oxidation inhibition coupled with β-carotene, appears very useful as a mimetic model of lipid peroxidation in biological membranes. β-carotene-linoleic acid assay determines the inhibition ratios of linoleic acid oxidation as further methods to confirm the anti-lipoperoxidation effects of V. negundo and V. trifolia .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the degradation rate of β-carotene-linoleate depends on the antioxidant activity of the extracts. According to Boumerfeg et al [ 22 ], the test of linoleic acid oxidation inhibition coupled with β-carotene, appears very useful as a mimetic model of lipid peroxidation in biological membranes. β-carotene-linoleic acid assay determines the inhibition ratios of linoleic acid oxidation as further methods to confirm the anti-lipoperoxidation effects of V. negundo and V. trifolia .…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that the ASE improve free radical scavenging activity and reducing capacity regardless of the importance of these activities of the ASE determined in-vitro and these effects may be primarily attributed to the polyphenolic contents. According to the literature, many types of research demonstrate the significant correlation between the measured plasma antioxidant capacity and the total phenol content of plant extracts 25,26,27 . Whereas, in-vivo these activities are limited by several factors such as low bioavailability and metabolic conversion of the absorbed polyphenols (plasma concentration rarely exceeds 1µM) 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that quercitin have a stronger scavenger activity compared to rutin, this decrease in activity of rutin may be caused by the blockage of the hydroxyl groups by glycosylation (Rutinose) in carbons of positions 3. 23 . However, in our study, the order of decreasing scavenging activity among the C. calcitrapa extracts was found to be EAE > CrE > ChE, which is not in accordance with the amount of phenolic compounds present in these extracts.…”
Section: In Vitro Antioxidant Activity Dpph Radical Scavenging Activitymentioning
confidence: 99%